2014
DOI: 10.1371/journal.pone.0092692
|View full text |Cite
|
Sign up to set email alerts
|

DNA Compaction Induced by a Cationic Polymer or Surfactant Impact Gene Expression and DNA Degradation

Abstract: There is an increasing interest in achieving gene regulation in biotechnological and biomedical applications by using synthetic DNA-binding agents. Most studies have so far focused on synthetic sequence-specific DNA-binding agents. Such approaches are relatively complicated and cost intensive and their level of sophistication is not always required, in particular for biotechnological application. Our study is inspired by in vivo data that suggest that DNA compaction might contribute to gene regulation. This st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(39 citation statements)
references
References 74 publications
1
38
0
Order By: Relevance
“…Here we note that we recently showed that a highly charged polyelectrolyte, heparin, can be used to release nucleic acids from complexes with dendrimers. 49 …”
Section: Resultsmentioning
confidence: 99%
“…Here we note that we recently showed that a highly charged polyelectrolyte, heparin, can be used to release nucleic acids from complexes with dendrimers. 49 …”
Section: Resultsmentioning
confidence: 99%
“…Cationic surfactants can condense high molecular DNA in solutions to produce nanosized particles [ 1 , 2 , 3 , 4 , 5 , 6 , 7 ]. DNA condensation induced by a variety of agents is an important stage in gene delivery technique [ 8 , 9 , 10 ]. The compact structures are typically observed in the excess of cationic surfactant in DNA solution at a sufficiently high charge ratio z (the number of positive groups of surfactants per a single DNA phosphate) [ 4 , 5 , 7 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…It is known that the complexes of oppositely charged polymers and surfactants in water can be used for the formation of different structures. For example, DNA complexes with cationic surfactants in aqueous solution represent an attractive platform for the design of functional nanostructures . The formation of DNA complexes with azobenzene containing photosensitive surfactants is especially attractive due to the possibility to reach reversible DNA compaction employing UV–Vis irradiation of the complexes.…”
Section: Introductionmentioning
confidence: 99%
“…For example, DNA complexes with cationic surfactants in aqueous solution represent an attractive platform for the design of functional nanostructures. 19,20 The formation of DNA complexes with azobenzene containing photosensitive surfactants is especially attractive due to the possibility to reach reversible DNA compaction employing UV-Vis irradiation of the complexes. The surfactant undergoes reversible photoisomerization between more hydrophobic trans-(in the dark and under blue light illumination) and more hydrophilic cis-(under UV light illumination) form because of the presence of photoresponsive azobenzene unit.…”
Section: Introductionmentioning
confidence: 99%